Zakat and Accounting Valuation Model - Ries Ahmed, Essia; Halim Bin Aiffin, Ku; Yousif Alabdullah, Tariq Tawfeeq; Zuqebah, Ahmed (Journal of Reviews on Global Economics, 2016)
The valuation and measurement of assets with regard to Zakat is necessary issue from Islamic perspective. Therefore, re-value the assets regularly is needed and Islamic accounting system probably uses both historical and market selling prices with regard to enable firms to accommodate contracts and to discharge with social responsibility. Zakat accounting includes the accounting principles that relate not only to measurement and valuation but also recording, interpreting, presentation and disclosure of accounting information. Thus, the main objective of this paper is to elaborate the importance of Islamic accounting valuation adopted in zakat regard to accounting models. The application and mechanics of zakat and valuation model discussed related to the implementation of the current practices of accounting and valuation models that adopted in Islamic firms.